Проблематика та переваги дистанційного навчання в умовах пандемії у закладах вищої освіти - Резниченко, А. А.; Шарова, Тетяна Михайлівна; Шарова, Татьяна Михайловна; Sharova, Tetiana (My University, 2021)
UK: У статті проаналізовано дистанційне навчання у контексті викликів сучасної університетської освіти; представлено можливість виокремлення можливих переваг та недоліків освітнього дистанційного процесу; представляємо науковій спільноті проблеми дистанційної освіти в Україні, оскільки маємо порівняльний аналіз дистанційної та очної форм навчання. EN: The article analyzes distance learning in the context of the challenges of modern university education; the ability to identify all possible advantages and disadvantages of the educational distance process; we present to the scientific community the problems of distance education in Ukraine, as we have a comparative analysis of distance and full-time forms of learning.
Problems and Benefits of Distance Learning in a Pandemic Condition in Higher Education Institutions
Keywords: дистанційне навчання; Інтернет; інформаційні технології; форма навчання; он-лайн; distance learning; Internet; information technologies; forms of learmimg; online